Security Practices of Higher Education Institutions in Ilocos Norte, Philippines in the Upsurge of Coronavirus - Pacapac, Marlow Timbreza (FKIP Universitas Lampung, 2022)
To analyze the security practices of Higher Education Institutions in the province of Ilocos Norte, Philippines during the surge of the COVID-19 disease is the objective of this study. The researcher used qualitative methodology using action research design through the strengths, weaknesses, opportunities, and threats (SWOT) approach. Study participants were members of security management of three HEIs selected thru purposive sampling. The result of the study showed that the security management of the Institutions guarantees the security of all stakeholders in all areas of security covered in the study by complying with all COVID-19 health and security protocols. However, the upsurge of the COVID-19 pandemic causes dangerous threats to the institutions' areas of security. It can be concluded that the SWOT of Higher Educations Institutions' security practices is diverse on all areas of security. There are challenges that the security management of HEIs encountered during the outbreak of COVID-19. Keywords: COVID-19, security practices, higher education institution, pandemic.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202235